Marine karst environment characterization using joint geophysical and geotechnical data. Issue 4 (6th June 2022) - Dusart, Judith; Tarits, Pascal; Bazin, Sara; Isorna, Rocio; d'Eu, Jean‐François
ABSTRACT: Submarine karstic environments are complex and challenging to study. Seismic investigations usually have difficulty getting geological information because of a lack of penetration due to the high reflectivity of the calcareous substratum. To circumvent this problem, we studied how to combine marine electrical resistivity tomography (MERT) with geotechnical data to investigate the porosity structure from the geotechnical to the geophysical scale. We applied the technique to the submarine karstic plateau of Banc de Guérande (Saint‐Nazaire, France), which is mainly composed of hard calcarenite and sandy pockets. We obtained sections of two‐dimensional resistivity models from the MERT data inversion. We used existing geotechnical data on extracted cores at several boreholes close to the MERT profiles using a multi‐sensor core logging (MSCL) bench. We used porosity proxies derived from Archie's law and porosity data from the MSCL inferred from gamma density measurements on the core to combine the data of very different scales (metre for MERT and centimetre for MSCL). The comparison between measurements showed a good similarity between in situ MERT and borehole MSCL data at depths greater than ∼10 m below the seafloor. A larger difference was observed close to the seabed, where the MERT porosity was higher than the MSCL porosity. The extraction of water‐saturated cores and the numerous core fractures could explain this difference near the surface. The results were analysed with respect to the scale difference between geophysical and geotechnical data. The conclusions suggested that the difference between MERT and MSCL porosities could be testified from the local heterogeneity of the soil and indicated whether the surrounding substratum was more porous (and thus fractured or dissolved) than the core or vice versa. The study highlighted the necessity of an excellent collocation of the data to retrieve reliable information from the comparison between geophysical and geotechnical data.